This thesis documents the development of a multi-effects unit for electric guitars. After the description of the essential fundamentals, the requirements of the unit are defined. On that basis, the design and implementation phase is described. In conclusion, the results of appropriate system- and component tests are evaluated. - Thorben Kay (Hochschule für angewandte Wissenschaften Hamburg, 2018)
This thesis documents the development of a multi-effects unit for electric guitars. After the description of the essential fundamentals, the requirements of the unit are defined. On that basis, the design and implementation phase is described. In conclusion, the results of appropriate system- and component tests are evaluated.